Definition of quality’s criteria of root canal’s sealing using cone-beam computed tomography (Эндодонтия Today, 2020)
Successful treatment of root canals has a big value in endodontic practice. In response with wide introduce of cone-beam computed tomography in clinical cases, it is necessary to update the criteria of quality obturation, which were created for two-dimensional x-ray images.